已知│a+b-1│=1,求代数式(a+b-1)³+2(a+b-1)²-a-b的值.(应该有两种做法)

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/20 20:26:07
已知│a+b-1│=1,求代数式(a+b-1)³+2(a+b-1)²-a-b的值.(应该有两种做法)

已知│a+b-1│=1,求代数式(a+b-1)³+2(a+b-1)²-a-b的值.(应该有两种做法)
已知│a+b-1│=1,求代数式(a+b-1)³+2(a+b-1)²-a-b的值.(应该有两种做法)

已知│a+b-1│=1,求代数式(a+b-1)³+2(a+b-1)²-a-b的值.(应该有两种做法)
(a+b-1)³+2(a+b-1)²-a-b=(a+b-1)³+2(a+b-1)²-(a+b-1)-1
若a+b-1=1,则(a+b-1)³+2(a+b-1)²-(a+b-1)-1=1+2-1-1=1
若a+b-1=-1,则(a+b-1)³+2(a+b-1)²-(a+b-1)-1=-1+2+1-1=1
所以(a+b-1)³+2(a+b-1)²-a-b=1

方法一:
│a+b-1│=1
(1)a+b=2
(a+b-1)³+2(a+b-1)²-a-b
=1+2-2=1
(2)a+b=0
(a+b-1)³+2(a+b-1)²-a-b
=-1+2-0=1
(a+b-1)³+2(a+b-1)²-a-b=1
方法二:

全部展开

方法一:
│a+b-1│=1
(1)a+b=2
(a+b-1)³+2(a+b-1)²-a-b
=1+2-2=1
(2)a+b=0
(a+b-1)³+2(a+b-1)²-a-b
=-1+2-0=1
(a+b-1)³+2(a+b-1)²-a-b=1
方法二:
│a+b-1│=1 (a+b-1)^2=1
(a+b-1)^3=(a+b-1)^2(a+b-1)=1*(a+b-1)=a+b-1
(a+b-1)^3-(a+b-1)=0
(a+b-1)³+2(a+b-1)²-a-b
=(a+b-1)³+2(a+b-1)²-a-b+1-1
=[(a+b-1)^3-(a+b-1)]+2(a+b-1)²-1
=0+2-1
=1
(a+b-1)³+2(a+b-1)²-a-b=1

收起

原式=(a+b-1)+2-a-b
=1
补充:注意到(a+b-1)²=1

都做好了 同意三楼的!!